The impact of instrumental stakeholder management on blockchain technology adoption behavior in agri-food supply chains - Michael Paul Kramer; Linda Bitsch; Jon Hanf (Journal of Risk and Financial Management, 2021)
Coffee is the second most important commodity in terms of global trade value, with its global market value exceeding 460 billion in 2020. Its supply networks, which encompass multiple stakeholders, are complex and nontransparent. Blockchain is a trust technology, and some coffee firms have embraced this technology to provide trust attributes to consumers while making their supply chain more transparent. For businesses to gain the expected productivity advantages, a technology must be adopted and used. As theoretical and empirical research on blockchain technology adoption is scarce, this article attempts to identify behavioral intentions of stakeholders in the supply network toward its adoption. Based on exploratory interviews, this article develops a blockchain technology adoption model based on factors relevant to individuals' use behavior. The results provide evidence that a normative stakeholder management approach positively impacts use behavior. Managers can use the model to benchmark and improve their corporate social responsibility strategy to obtain better returns on blockchain investments. This study closes a research gap as, to the best of the authors' knowledge, no research has been conducted so far on the impact of an instrumental stakeholder management approach on blockchain technology adoption behavior. Understanding how stakeholder management can compensate for the lack of consensus mechanisms in private and consortium blockchains, as well as understanding the factors influencing behavioral intentions toward the use of a technology, can provide for managerial guidance toward the development of an effective stakeholder management strategy, which eventually can result in a competitive advantage.
Keywords: 330; blockchain; technology adoption; food industry; supply chain; stakeholder management